Territorial Diagnosis Of Algeria; An Essay Of A Principal Component Analysis - Remmas, Mohamed Amine (جامعة الوادي - University of Eloued, 2021)
To understand and manage a territory, it is necessary to understand it in all its aspects. Faced with the complexity of the processes, development professionals today need new keys to understand and support actors in the field and decision-makers in the design and implementation of actions promoting development dynamics. Territorial diagnosis is a technique intended to measure, evaluate and model the various development issues. It leads to the promotion and enhancement of territories. This research has set the objective of developing a territorial diagnosis of Algeria with its forty eight wilayas. We supported our study with a principal component analysis (PCA). This allowed us to define the characteristics of the different regions of Algeria and presented the diversity of Algerian territory
مقال
Keywords: Territorial diagnosis ; Development, territory ; Principal Component Analysis (PCA) ; Territorial Typology ; Algeria